The Role of Optical Coherence Tomography Angiography in Optic Nerve Head Edema: A Narrative Review - Narges Karrabi; Sadid Hooshmandi; Alireza Amirabadi; Danial Roshandel; Kiana Hassanpour; Mohammad Pakravan (Journal of Ophthalmology)
Optic nerve head (ONH) edema is a clinical manifestation of many ocular and systemic disorders. Ocular and central nervous system imaging has been used to differentiate the underlying cause of ONH edema and monitor the disease course. ONH vessel abnormalities are among the earliest signs of impaired axonal transportation. Optical coherence tomography angiography (OCTA) is a noninvasive method for imaging ONH and peripapillary vessels and has been used extensively for studying vascular changes in ONH disorders, including ONH edema. In this narrative review, we describe OCTA findings of the most common causes of ONH edema and its differential diagnoses including ONH drusen.